Use of Library Portal by Research Scholars of Indian Institute of Technology (IITs): A Comparative Study of Patna and Guwahati - Fatima, Nishat; Gulnaz; Hasaney, Sana (Journal of Information and Knowledge, 2019)
The paper presents result of a questionnaire based survey of use of library portal by research scholars of IITs Patna and Guwahati. The findings revealed that majority of research scholars used library portal in IIT Patna and IIT Guwahati. The study identifies some problems faced by Guwahati research scholars. A few suggestions are made for further improvement and enrichment of the library portals to cater to the needs of the researchers.